The Development of Contextual-Based Science Learning Modules to Improve Student's Science Literacy - Nadhifah, Naurah; Wahyuni, Sri; Wicaksono, Iwan (International Journal of Education, Information Technology, and Others, 2025)
This research is motivated by the low scientific literacy skills of junior high school students. One of the causes of the low scientific literacy skills of students is the lack of teaching materials that can shape students' scientific literacy skills. The available teaching materials have limitations in the relevance of learning materials to problems in everyday life. Therefore, a module was developed that is integrated with the problems in Kemiri Village to develop students' scientific literacy skills. This study aims to examine the validity and readability of contextual-based modules to develop scientific literacy of junior high school students. The type of research used is development research with the ADDIE design model. The subjects of the study were 3 science teachers as validators and students of Class VIII of SMP Negeri 1 Panti, Jember. Based on the validation results, the contextual-based module obtained a content validation percentage of 92.55% and a construct validation of 92.00% which is included in the very valid criteria. The readability of the contextual-based module obtained a readability percentage of 90.38%, also included in the easy criteria. Based on the research results, it can be concluded that the contextual-based science learning module to develop science literacy is feasible to be applied in science learning and can develop the science literacy of junior high school students.